A case report on ventrolateral herniorrhaphy in sheep: The novel way of using vest‐over‐pants closure technique. Issue 6 (14th August 2021) - Kitessa, Jiregna Dugassa; Merga, Abebe Fromsa; Afata, Abebe Wirtu
Abstract: Objectives: To describe the surgical management of ventrolateral hernias by using the vest‐over‐pants closure technique. Animals: On two local breed sheep that were kept under an extensive management system. Study design: Case report. Study methods: Patient history and clinical findings, diagnosis, and treatment. Outcomes: After frequent follow‐up and well post‐operative care, the patient were recovered. Conclusion: The herniorrhaphy and closure performed in both sheep were highly successful and effective in apposing hernial ring by maintaining equal tensions with minimal wound dehiscence, unlike other closure techniques. Abstract : A case report on ventrolateral herniorrhaphy in ovines.